PENGARUH DEPRESIASI NILAI RUPIAH PADA RETURN SAHAM DAN VOLUME PERDAGANGAN SAHAM PERUSAHAAN MULTINASIONAL DI BURSA EFEK INDONESIA - Malindasari, Putu; Sukartha, I Made; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The important of capital market to the national economy makes the Indonesia Stock Exchange (IDX) as a leading economic indicator that is also influenced by micro and macro factors causing the fluctuation of stock prices. The depreciation of the rupiah as macroeconomic factor could affect on stock return and trading volume activity. This research aims to determine the effect of the depreciation of rupiah in stock return and trading  volume activity. Population of sample  are for all companies  listed on the Indonesia Stock Exchange in 2013. Election method using purposive sampling to obtain 58 firms sample. This research uses an event study as its method within a seven day event windows. The event is the hightest  the depreciation of the rupiah every month in 2013. The market reaction is measured by abnormal return and trading volume activity. The study used paired sample t- test and  the result show that there are differences in stock return before and after the depreciation of the rupiah. But there are not diferences trading volume activity before and after the depreciation of the rupiah.
Keywords: depreciation of the rupiah, abnormal return and trading volume activity